2017
DOI: 10.1183/13993003.02055-2016
|View full text |Cite
|
Sign up to set email alerts
|

Maximal mid-expiratory flow detects early lung disease in α1-antitrypsin deficiency

Abstract: Pathological studies suggest that loss of small airways precedes airflow obstruction and emphysema in chronic obstructive pulmonary disease (COPD). Not all α-antitrypsin deficiency (AATD) patients develop COPD, and measures of small airways function might be able to detect those at risk.Maximal mid-expiratory flow (MMEF), forced expiratory volume in 1 s (FEV), ratio of FEV/forced vital capacity (FVC), health status, presence of emphysema (computed tomography (CT) densitometry) and subsequent decline in FEV wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 42 publications
4
55
0
Order By: Relevance
“…There are many subtypes of AATD but in the most common severe form of deficiency (named PiZZ) this leads to mis-folding of the protein product, retention of AAT in AAT-producing cells and the formation of protein polymers in these cells, which causes damage and low circulating levels of AAT. AATD is the only robustly established genetic risk factor for the development of COPD and emphysema, and these disease processes can occur in patients with AATD, even in the absence of cigarette smoking 62, 91, 95, 96 .…”
Section: Alpha-1 Anti-trypsin Deficiencymentioning
confidence: 99%
“…There are many subtypes of AATD but in the most common severe form of deficiency (named PiZZ) this leads to mis-folding of the protein product, retention of AAT in AAT-producing cells and the formation of protein polymers in these cells, which causes damage and low circulating levels of AAT. AATD is the only robustly established genetic risk factor for the development of COPD and emphysema, and these disease processes can occur in patients with AATD, even in the absence of cigarette smoking 62, 91, 95, 96 .…”
Section: Alpha-1 Anti-trypsin Deficiencymentioning
confidence: 99%
“…However, despite the limitations of MMEF, it may still be useful as a stand-alone measure in certain patient cohorts as a marker of early airflow limitation before the spirometric criterion for COPD is reached. 13 , 23 Topalovic et al 23 extended this concept by analyzing the shape of the flow-volume curve and demonstrated that the angle of inflection between the two best fitting regression lines of the expiratory curve with a cutoff angle of <131° was highly specific (97%), although less sensitive (51%), for the presence of emphysema in COPD. This angle of inflection (or “spirographic kink”) reflects the dynamic airways collapse due to the loss of lung connective tissue in emphysema (notably elastin) that usually maintains airway patency during forced expiration in healthy individuals.…”
Section: Expiratory Flowsmentioning
confidence: 99%
“…In addition, abnormal tests were associated with impaired health status and predicted the subsequent rate of decline of FEV 1 . 13 …”
Section: Introductionmentioning
confidence: 99%
“…ECG captures the electrical activity of the heart as a time series data with Ag/AgCl electrodes attached to exposed bare skin; this will cause restraint and produce some burdens to subjects [3]. Airflow is another popular measuring vital sign (respiratory) method with common sensors fixed at the nasal cavity or the chest [4]. Video camera methods run the gamut ranging from high-end expensive camera systems that track bright objects placed on the chest and used in CT image gating to low-cost vital signs "apps" for mobile devices that give heart rate by detecting facial flushing with each beat and respiration rate by chest movement [5].…”
Section: Introductionmentioning
confidence: 99%